2009
DOI: 10.1002/ijc.24367
|View full text |Cite
|
Sign up to set email alerts
|

WT1 IgG antibody for early detection of nonsmall cell lung cancer and as its prognostic factor

Abstract: There are urgent needs to develop methods for early detection of nonsmall cell lung cancer (NSCLC) because of its increasing incidence and poor prognosis. Here, we analyzed the production of IgG antibody (WT1 Ab) against WT1 (Wilms' tumor gene) protein that was overexpressed in the majority of NSCLC. Enzymelinked immuno-sorbent assay showed that WT1 Ab was produced in all of 91 NSCLC patients and 70 healthy individuals and that WT1 Ab titers were significantly higher in NSCLC patients compared with healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…In addition, leukemia stem cells have been shown to express WT1, which supports the superiority of WT1 as a cancer antigen, because it indicates the possibility that WT1-directed immunotherapy can target cancer stem cells (Saito et al 2010 ). Furthermore, a series of investigations using clinical samples such as patients' peripheral blood demonstrated that WT1-directed cellular and humoral immune responses were generated in patients with malignancies (Sugiyama 2001(Sugiyama , 2002(Sugiyama , 2005(Sugiyama , 2010Oka et al 2006Oka et al , 2007Oka et al , 2008aOka et al , b , 2009Oka and Sugiyama 2010 ;Elisseeva et al 2002 ;Wu et al 2005 ;Oji et al 2009 ). These preclinical results urged us to perform a WT1-targeting cancer immunotherapy trial, and we started a WT1 peptide vaccine clinical trial in 2001 and demonstrated that WT1 peptide can induce WT1-specifi c immunologic responses and the associated clinical responses (Sugiyama 2001(Sugiyama , 2002(Sugiyama , 2005(Sugiyama , 2010Oka et al 2003Oka et al , 2004Oka et al , 2006Oka et al , 2007Oka et al , 2008aOka et al , b , 2009Oka and Sugiyama 2010 ;Tsuboi et al 2004Tsuboi et al , 2007Tsuboi et al , 2012Morita et al 2004 ;Iiyama et al 2007 ;Kawakami et al 2007 ;Izumoto et al 2008 ;Ohta et al 2009 ;Hashii et al 2010Hashii et al , 2012Chiba et al 2010 ).…”
Section: Wilms' Tumor Gene Wt1 and The Background For Wt1 Gene Producmentioning
confidence: 90%
“…In addition, leukemia stem cells have been shown to express WT1, which supports the superiority of WT1 as a cancer antigen, because it indicates the possibility that WT1-directed immunotherapy can target cancer stem cells (Saito et al 2010 ). Furthermore, a series of investigations using clinical samples such as patients' peripheral blood demonstrated that WT1-directed cellular and humoral immune responses were generated in patients with malignancies (Sugiyama 2001(Sugiyama , 2002(Sugiyama , 2005(Sugiyama , 2010Oka et al 2006Oka et al , 2007Oka et al , 2008aOka et al , b , 2009Oka and Sugiyama 2010 ;Elisseeva et al 2002 ;Wu et al 2005 ;Oji et al 2009 ). These preclinical results urged us to perform a WT1-targeting cancer immunotherapy trial, and we started a WT1 peptide vaccine clinical trial in 2001 and demonstrated that WT1 peptide can induce WT1-specifi c immunologic responses and the associated clinical responses (Sugiyama 2001(Sugiyama , 2002(Sugiyama , 2005(Sugiyama , 2010Oka et al 2003Oka et al , 2004Oka et al , 2006Oka et al , 2007Oka et al , 2008aOka et al , b , 2009Oka and Sugiyama 2010 ;Tsuboi et al 2004Tsuboi et al , 2007Tsuboi et al , 2012Morita et al 2004 ;Iiyama et al 2007 ;Kawakami et al 2007 ;Izumoto et al 2008 ;Ohta et al 2009 ;Hashii et al 2010Hashii et al , 2012Chiba et al 2010 ).…”
Section: Wilms' Tumor Gene Wt1 and The Background For Wt1 Gene Producmentioning
confidence: 90%
“…GST-WT1 and GST-del-WT1 were produced according to the methods described previously. (20) Briefly, full-length WT1 and part of the WT1 gene corresponding to amino acids 180-324 were ligated into the pGEX-5X-3 vector (GE Healthcare, Buckinghamshire, UK) and transfected into E. coli. After collection of bacterial cells and extraction of the protein, GST-WT and GST-delWT1 protein were purified and used for western blotting analysis.…”
Section: Methodsmentioning
confidence: 99%
“…WT1 is highly expressed in various malignancies and has been found to perform oncogenic function [15,16] . Both cellular and humoral immune responses against WT1 are naturally elicited in cancer patients, indicating strong immunogenicity of WT1 [17,18] . Several clinical studies using WT1 peptide-based immunotherapies have been performed with encouraging results for patients, including children, with various kinds of malignancies [19,20] .…”
Section: Vascular Endothelial Cells Vegfr1 Vegfr2mentioning
confidence: 99%